Cuando el aprendizaje basado en la práctica profesional no provoca un interés laboral - Calvo Palomares, Ricard; Payá Castiblanque, Raúl; Sigalat Signes, Enric (Revista Fuentes, 2021)
El presente artículo muestra una experiencia de innovación docente en educación superior basada en el uso de tecnologías profesionales llevadas al ámbito educativo. Concretamente del aplicativo informático y la metodología utilizados profesionalmente por CEAL-Asociación Española de Auditores Sociolaborales en el desarrollo de su labor, y que ha permitido profesionalizar la docencia y aproximarla a la realidad del colectivo profesional (la vinculación entre lo académico y lo profesional que se convierte en un elemento esencial para impulsar la calidad educativa de la Universidad actual). Pese a ello, pone de manifiesto una situación paradójica, que el alumnado valora la propuesta metodológica como altamente positiva, útil, aplicada y práctica, pero, por el contrario, mayoritariamente se ha observado que no tienen la percepción de que la actividad como auditor/a sociolaboral sea una posible salida profesional futura para ellos (cuando es una de las 7 salidas profesionales establecidas en el Libro Blanco para el Grado de Relaciones Laborales y Recursos Humanos). Abstract The link between the academic and the professional has become an essential element in promoting the educational quality of today's University. This article shows an experience of teaching innovation in higher education based on the use of professional technologies brought to the educational field. Specifically, the computer application and methodology used professionally by CEAL-Spanish Association of Socio-Labour Auditors in the development of their work, and which has allowed the professionalization of teaching and bringing it closer to the reality of the professional collective. A questionnaire was used to find out the students' perception of the methodological proposal and its potential transfer to the professional field. In addition, the vision of the participating companies was incorporated by asking them about their possible transference. Ambivalent results were found. On the one hand, the students valued the methodological proposal as highly positive, useful, applied and practical, but, on the other hand, they did not perceive that the activity as a socio-labour auditor is a possible future professional outlet, when it is one of the 7 professional outlets established in the White Paper for the Degree in Labour Relations and Human Resources. In conclusion, the positive effect in the educational sphere did not have the desired impact in the professional sphere due to external factors related to the business context, since none of the collaborating companies had previously carried out any socio-labour audit, nor were they aware of the tools and methods for carrying it out.